An optimal proportion of mixing broad‐leaved forest for enhancing the effective productivity of moso bamboo. Issue 8 (17th March 2015) - Cheng, Xiao‐Fei; Shi, Pei‐Jian; Hui, Cang; Wang, Fu‐Sheng; Liu, Guo‐Hua; Li, Bai‐Lian
Abstract: Moso bamboos ( Phyllostachys edulis ) are important forestry plants in southern China, with substantial roles to play in regional economic and ecological systems. Mixing broad‐leaved forests and moso bamboos is a common management practice in China, and it is fundamental to elucidate the interactions between broad‐leaved trees and moso bamboos for ensuring the sustainable provision of ecosystem services. We examine how the proportion of broad‐leaved forest in a mixed managed zone, topology, and soil profile affects the effective productivity of moso bamboos (i.e., those with significant economic value), using linear regression and generalized additive models. Bamboo's diameter at breast height follows a Weibull distribution. The importance of these variables to bamboo productivity is, respectively, slope (25.9%), the proportion of broad‐leaved forest (24.8%), elevation (23.3%), gravel content by volume (16.6%), slope location (8.3%), and soil layer thickness (1.2%). Highest productivity is found on the 25° slope, with a 600‐m elevation, and 30% broad‐leaved forest. As such, broad‐leaved forest in the upper slope can have a strong influence on the effective productivity of moso bamboo, ranking only after slope and before elevation. These factors can be considered in future management practice. Abstract : (1) Hardwoods can significantly affect the productivity of moso bamboo. (2) Other environmental factors can also influence the average biomass of moso bamboo.